1998
DOI: 10.1021/bi972930+
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Calmodulin Alters Its Potency as an Activator of Target Enzymes

Abstract: Previous work has shown that calmodulin (CaM) is constitutively phosphorylated in rat liver, probably by casein kinase II [Quadroni, M., James, P., and Carafoli, E. (1994) J. Biol. Chem. 269, 16116-16122]. A procedure is now described for the isolation of the phosphorylated forms of calmodulin (PCaM) free from CaM, since in vitro phosphorylation experiments yield a 50:50 mixture of 3-4 times phosphorylated CaM and native CaM. The activation of six target enzymes by PCaM was tested: myosin light chain kinase, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
5
46
0
Order By: Relevance
“…tinct from the reported effects on neuronal NOS (nNOS) kinetics: Quadroni et al (27) found that in vitro CK2 treatment of CaM increases the nNOS maximal activity. Although eNOS and nNOS have similar features, their amino acid sequences are only 60% identical.…”
Section: Discussionmentioning
confidence: 99%
“…tinct from the reported effects on neuronal NOS (nNOS) kinetics: Quadroni et al (27) found that in vitro CK2 treatment of CaM increases the nNOS maximal activity. Although eNOS and nNOS have similar features, their amino acid sequences are only 60% identical.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of CaM decreases its affinity for target substrates (378), and mutation of the conserved phosphorylation site in CaBP1 resulted in even greater [Ca 2ϩ ] i signaling inhibition (225). Although this site is not conserved in CIB1, it remains possible that phosphorylation, other covalent modifications, and other protein interactions could regulate the affinities of the interactions of CaBP1 and CIB1 with the InsP 3 R. Unbinding of the protein ligands could enable the channel to escape from inactivation, allowing the channel to again be activated by protein ligand rebinding, in a mechanism of repeated channel activation that is completely independent of InsP 3 .…”
Section: Cabp and Cib1mentioning
confidence: 99%
“…Phosphorylation of Ca 2ϩ -binding proteins, including CaM, can affect their Ca 2ϩ -binding capability and interaction with target proteins (Benaim and Villalobo, 2002). Casein kinase 2 (CK2) phosphorylates several amino acid residues in CaM, including serine 101, which decreases the affinity of CaM for its substrates (Quadroni et al, 1998;Bildl et al, 2004;Kasri et al, 2004;Allen et al, 2007). Similar to CaM, an analogous residue (Serine 120) in CaBP1 is phosphorylated by casein kinase 2, which weakens the effect of CaBP1 in inhibiting Ca 2ϩ release by the IP 3 receptor (Kasri et al, 2004).…”
Section: Introductionmentioning
confidence: 99%